Participatory approaches to weather forecasting in Baringo County - International Livestock Research Institute (International Livestock Research Institute, 2024)
Increasingly erratic weather patterns necessitate strengthening forecasts with time sensitive, scientific weather predictions and crop and livestock advisories. To address this, the Kenya Meteorological Department (KMD) has adopted participatory scenario planning (PSP), which is a mechanism for collective sharing and interpretation of climate information for informed decision-making tailored to specific communities. PSP plays an important role in decision-making, supporting farmers and pastoralists in their seasonal activities by providing essential information to guide crop type and variety selection as well as livestock management.